Pengaruh Latihan Metode Drill terhadap Peningkatan Keterampilan Pivot dalam Pertandingan Basket pada Kegiatan Ekstrakurikuler SMA Negeri 1 Kepahiang - Yasir, Muhammad Irfan; Ajayati, Titi; Sumantri, Ajis (Educative Sportive, 2025)
This study aims to determine the effect of drill method training on pivot skills in extracurricular basketball activities of students at SMA Negeri 1 Kepahiang. This study used a pre-experimental design with the "One Group Pretest-Posttest Design" design, which is a design that uses pretest and posttest so that the difference in results due to the treatment given can be known with certainty. The population used in this study were students who took part in extracurricular basketball at SMA Negeri 1 Kepahiang as many as 27 people and the research sample used Simple Random Sampling, which is a sampling technique that is carried out randomly from members of the population without considering the existing strata, namely 27 people. The statistical analysis used in this study was the t-test to test the hypothesis that there was an effect of drill method training on pivot skills in extracurricular basketball activities of students at SMA Negeri 1 Kepahiang. The results of the calculation analysis showed a significant effect on the pivot results. The calculation results state that the calculation of the t-value calculation is -15.060 > t-table 1.708 with a level of α = 0.05, meaning that there is a significant influence between X (drill training) and Y (increasing pivot skills) with a percentage of 31%. Based on the hypothesis testing that has been carried out, it states that there is a significant influence in drill method training on pivot skills in the basketball extracurricular of students at SMA Negeri 1 Kepahiang.